"Teacher factors as predictors of nursery pupils’ socio- emotional skills development " (2014)
It is pertinent to note that at the early childhood stage, children need to be sociable and emotionally balanced. Research shows that those children who find it difficult to succeed in school may have socio-emotional problems. This study investigated teacher factors as determinants of nursery two pupils’ socio-emotional skills development (teacher factors - gender, job satisfaction, attitude, qualification; school location and leaner gender). The study is a survey type which used observational technique. One hundred and ninety-two teachers in 96 public and private nursery schools and their pupils (384) participated. Two instruments; Teachers’ Questionnaire (TEQ) and Pupil’s Socio-Emotional Skills Scale (PSESS) were used. Multiple Regression was used to analyse the data at p<0.05 level of significance. The six predictor variables jointly contributed significantly towards pupils social skills development F(6,185)=3.398, and emotional development [F(6,185)=4.189], at P<.05]. The effects of the relationship on social skill development is shown in the value of the coefficient (R)=.315, R2 = .099 and the Adjusted R2=.070 indicating that 7% of the total variation in pupil’s social skills development was accounted for by combined contribution of the six variables. However, only two variables; teacher’s gender [b = .151, t(185) = 2.120, p< .05] and teacher’s job satisfaction level [(3 = .233, t(185) = 3.027, p< .05] had significant contribution. Emotional skills development had coefficient multiple regression R = .346, R2 = .120* and Adjusted R2 = .091. Indicating that 12% of the total variation in pupil’s social skills development is attributable to the combined effect of the six indicators. However, only teacher’s job satisfaction level [b = .310, t(185) = 4.080, p< .05] contributed significantly to the prediction. The implication of the findings were discussed.